Endoplasmic reticulum refilling and mitochondrial calcium extrusion promoted in neurons by NCX1 and NCX3 in ischemic preconditioning are determinant for neuroprotection - Sisalli, M J (Nature Publishing Group, 2014)
Ischemic preconditioning (IPC), an important endogenous adaptive mechanism of the CNS, renders the brain more tolerant to lethal cerebral ischemia. The molecular mechanisms responsible for the induction and maintenance of ischemic tolerance in the brain are complex and still remain undefined. Considering the increased expression of the two sodium calcium exchanger (NCX) isoforms, NCX1 and NCX3, during cerebral ischemia and the relevance of nitric oxide (NO) in IPC modulation, we investigated whether the activation of the NO/PI3K/Akt pathway induced by IPC could regulate calcium homeostasis through changes in NCX1 and NCX3 expression and activity, thus contributing to ischemic tolerance. To this aim, we set up an in vitro model of IPC by exposing cortical neurons to a 30-min oxygen and glucose deprivation (OGD) followed by 3-h OGD plus reoxygenation. IPC was able to stimulate NCX activity, as revealed by Fura-2AM single-cell microfluorimetry. This effect was mediated by the NO/PI3K/Akt pathway since it was blocked by the following: (a) the NOS inhibitors L-NAME and 7-Nitroindazole, (b) the IP3K/Akt inhibitors LY294002, wortmannin and the Akt-negative dominant, (c) the NCX1 and NCX3 siRNA. Intriguingly, this IPC-mediated upregulation of NCX1 and NCX3 activity may control calcium level within endoplasimc reticulum (ER) and mitochondria, respectively. In fact, IPC-induced NCX1 upregulation produced an increase in ER calcium refilling since this increase was prevented by siNCX1. Moreover, by increasing NCX3 activity, IPC reduced mitochondrial calcium concentration. Accordingly, the inhibition of NCX by CGP37157 reverted this effect, thus suggesting that IPC-induced NCX3-increased activity may improve mitochondrial function during OGD/reoxygenation. Collectively, these results indicate that IPC-induced neuroprotection may occur through the modulation of calcium homeostasis in ER and mitochondria through NO/PI3K/Akt-mediated NCX1 and NCX3 upregulation.